Impact of environmental changes on Dermatology - Haddad Junior, Vidal [UNESP]; Mendes, Adriana Lucia [UNESP]; Talhari, Carolina Chrusciak [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2021)
Urbanization, pollution and the modification of natural landscapes are characteristics of modern society, where the change in human relations with the environment and the impact on biodiversity are environmental determinants that affect the health-disease relationship. The skin is an organ that has a strong interface with the environment and, therefore, the prevalence patterns of dermatoses may reflect these environmental changes. In this article, aspects related to deforestation, fires, urbanization, large-scale agriculture, extensive livestock farming, pollution and climatic changes are discussed regarding their influence on the epidemiology of skin diseases. It is important that dermatologists be aware of their social responsibility in order to promote sustainable practices in their community, in addition to identifying the impacts of environmental imbalances on different dermatoses, which is essential for the prevention and treatment of these diseases. (C) 2021 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Climatic variations; Environment; Pollution; Radiation; Sustainability; Urbanization